2016
DOI: 10.1016/j.tube.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal whole genome analysis of pre and post drug treatment Mycobacterium tuberculosis isolates reveals progressive steps to drug resistance

Abstract: Tuberculosis (TB) is one of the leading causes of death due to an infectious disease in the world. Understanding the mechanisms of drug resistance has become pivotal in the detection and treatment of newly emerging resistant TB cases. We have analyzed three pairs of Mycobacterium tuberculosis strains pre- and post-drug treatment to identify mutations involved in the progression of resistance to the drugs rifampicin and isoniazid. In the rifampicin resistant strain, we confirmed a mutation in rpoB (S450L) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…As it was expected based on previous genomic and western blot analyses [6,12], there was a statistically significant reduction of KatG levels in both clinical and laboratory INHr strains compared to their respective INHs progenitor strains (Table 1, Figure 2). KatG deficiency had been noted in a previous virulence study of these strains in the water-soluble fractions (CYT and CFP) by WB [6].…”
Section: Altered Proteins With the Same Trend Among The Mtb Clonal Pairssupporting
confidence: 84%
See 3 more Smart Citations
“…As it was expected based on previous genomic and western blot analyses [6,12], there was a statistically significant reduction of KatG levels in both clinical and laboratory INHr strains compared to their respective INHs progenitor strains (Table 1, Figure 2). KatG deficiency had been noted in a previous virulence study of these strains in the water-soluble fractions (CYT and CFP) by WB [6].…”
Section: Altered Proteins With the Same Trend Among The Mtb Clonal Pairssupporting
confidence: 84%
“…It is important to emphasize two points that should be considered in the analysis of the findings presented here, first, with the exception of KatG levels, none of the other protein changes described in this study have associated mutations in their respective genes, as previously revealed by whole genomics sequencing of these strains [12]. Second, this shotgun proteomics approach presents several limitations in that changes in protein abundance may be attributed to decreased expression, differences in protein half-lives, and losses in protein abundance due to aggregation and post-translational modifications with concomitant changes in protein function.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Mutation analysis in the katG gene previously done by PCR-sequencing [31] confirmed the mutations Val1Ala and Glu3Val for the clinical INHr strain and Val1Ala only for the laboratory INHr strain [30]. The Val1Ala mutation has been previously identified in clinical INHr TB cases [32, 33], while the Glu3Val is a novel mutation.…”
Section: Methodsmentioning
confidence: 79%